Peran Manajemen Keuangan Pada Usaha Mikro Kecil Dan Menengah (UMKM) Batik Dalam Memajukan Sektor Kewirausahaana - Nailariza Umami (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2019)
One of the steps taken by Indonesia based on the government's strategic plan to deal with MEA is to strengthen the Micro, Small and Medium Enterprises (MSME) sector. But in reality the knowledge of batik entrepreneurs is still low about the importance of financial management for the continuity of the business he initiated to be able to participate in free trade between countries in the Southeast Asian region to be a problem that must be resolved, so that Indonesia has a good opportunity to show product quality and quantity and Human Resources (HR) to other countries openly. In MSME management skills are very necessary, especially Financial Management. Financial management is all company activities related to businesses obtaining company funds with low costs and efforts to use and allocate these funds efficiently (Sutrisno: 3, 2009). For this reason, the purpose of this study was to determine the role of financial management in Batik Micro, Small and Medium Enterprises (UMKM) in filling the MEA (Asean Economic Community. This research included quantitative descriptive research carried out in Batik Satrio Micro Small and Medium Enterprises (UMKM) Manah Bangoan Village, Kedungwaru Subdistrict, Tulungagung District, is said to be because in this study only describes financial management in the Satrio Manah Batik Micro Small and Medium Enterprises (UMKM) .The respondents in this study were all 50 Satrio Manah Batik employees Data in this study are interviews, questionnaires, and documentation Data analysis is done by processing the scores of observations on financial statements and questionnaires.The results obtained by the researchers are management of financial management in Micro, Small and Medium Enterprises (UMKM) Batik Satrio Manah has not met the standard keu management good dreams, and there still needs to be improvement in accordance with financial management standards